Ventricular fibrillation arrest due to Brugada syndrome in a coronavirus disease 2019 patient with negative procainamide challenge: a case report. Issue 12 (8th November 2021) - Zou, Guangchen; Khanna, Mukul; Zahid, Saliha; Dengle, Samir; Matta, Bhavna; Zaheer, Haris; Farrell, Matthew; Stein, Russell
Abstract: Background: Pharmacologic challenge test is often used to diagnose Brugada syndrome (BrS) when spontaneous electrocardiograms (ECG) do not show type I Brugada pattern but reported sensitivity varies. The role of the exercise stress test in diagnosing Brugada syndrome is not well-established. Case summary: A patient had a type I Brugada pattern ECG during the recovery phase of exercise stress test but had a negative procainamide challenge test. He had a loop recorder implanted and later survived a ventricular fibrillation (VF) arrest provoked by coronavirus disease 2019 (COVID-19). Electrocardiogram on arrival showed type 1 Brugada pattern. He was discharged after implantable cardioverter-defibrillator implantation. He later underwent genetic testing and was found to be heterozygous for c.844C>G (p.Arg282Gly) mutation in the SCN5A gene. Discussion: Type 1 Brugada pattern ECG may be unmasked by ST-segment augmentation during recovery from exercise. Exercise stress test may play a role in the diagnosis of Brugada syndrome when suspicion for Brugada syndrome remains after a negative procainamide challenge test or if the patient has exercise-related symptoms. COVID-19 can unmask BrS and trigger a VF cardiac arrest.